Resource Provision of the Sustainable Development under Global Shocks - Tcvetkov, Pavel; Didenko, Nikolay (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint focuses on interdisciplinary research that reveals the problems of resource provision of the economy, both from the perspective of local projects and from the point of view of the creation of global infrastructure that contributes to the achievement of Sustainable Development Goals. Considerable attention is paid to the development of the Arctic territories as one of the most promising sources of mineral and fuel resources as of 2021. This reprint also includes selected papers from European Raw Materials Conferences 2020-2021, held despite the global COVID-19 pandemic, and will be published with the financial support of the International competence Centre for mining-engineering education under the auspices of UNESCO: - Russian-UK Raw Materials Dialogue (21-23 October 2020); - Russian-German Raw Materials Conference (30 November-1 December 2020).